2010
DOI: 10.1108/ssrp-02-2010-b0006
|View full text |Cite
|
Sign up to set email alerts
|

He’s Too Young to Learn About That Stuff: Anti-Racist Pedagogy and Early Childhood Social Studies

Abstract: Few early childhood teachers engage in critical and anti-racist forms of pedagogical practice, primarily on the basis of developmental and political concerns. With the exception of a few studies, little has been documented relative to early childhood teachers’ experiences while enacting this form of pedagogical practice. The purpose of this article is to examine my teaching experiences engaging in critical, anti-racist pedagogy through the development and implementation of a critical action research study/unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These findings speak to the need for pre-service educator and professional development training in the area of anti-racism and/or anti-bias approaches (Derman-Sparks, 1989;Derman-Sparks & Ramsey, 1985;Dunn, Kirova, Cooley, & Ogilvie, 2009;Han, 2013;Husband, 2010;MacNevin & Berman, 2016;MacNaughton & Davis, 2009;MacNaughton, & Hughes, 2007;Milner, 2010;Schoorman, 2011). MacNaughton and Davis (2009) explain that anti-racist pedagogies involve teaching and learning to challenge racism (also see Dei, 2003).…”
Section: Literature Review 'Race': Early Childhood Educator Practicesmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings speak to the need for pre-service educator and professional development training in the area of anti-racism and/or anti-bias approaches (Derman-Sparks, 1989;Derman-Sparks & Ramsey, 1985;Dunn, Kirova, Cooley, & Ogilvie, 2009;Han, 2013;Husband, 2010;MacNevin & Berman, 2016;MacNaughton & Davis, 2009;MacNaughton, & Hughes, 2007;Milner, 2010;Schoorman, 2011). MacNaughton and Davis (2009) explain that anti-racist pedagogies involve teaching and learning to challenge racism (also see Dei, 2003).…”
Section: Literature Review 'Race': Early Childhood Educator Practicesmentioning
confidence: 97%
“…Researchers report that educators who (implicitly or explicitly) take a colorblind approach or engage in colormuteness (Castagno, 2008;Pollock, 2004) do so for a number of reasons: an educator's own discomfort; the inaccurate belief that the children are 'too young' to understand race and racism; the belief that it is the parents' responsibility to teach children about race and racial bias; the belief that there is not enough time to devote to these issues; a lack of knowledge and/or unfamiliarity with available resources; and/or the belief that seeing and naming race makes one a racist (Bernhard et al, 1998;Boutte, 2008;Boutte, Lopez-Robertson, & Powers-Costello, 2011;Castagno, 2008;Connolly, 1995;Copenhaver-Johnson, 2006;Derman-Sparks & Ramsey, 2005;Husband, 2010Husband, , 2012Vittrup, 2016). Farago et al (2015) also point out that some White early childhood educators may not view race and racism as important concerns in today's society.…”
Section: Literature Review 'Race': Early Childhood Educator Practicesmentioning
confidence: 99%
“…Scholars also criticized how educators often underestimate children's capacity to understand race and racism (Doucet & Adair, 2013;Husband, 2010;Ryan & Grieshaber 2004;Park 2011, Ramsey 2004). Despite the belief that children would not be able to understand or discuss issues of race and racism, studies showed otherwise (Boutte, Lopez-Robertson, & Powers-Costello, 2011;Husband, 2010;Ryan & Grieshaber 2004;Van Ausdale & Feagin 2001).…”
Section: Race Talk In Early Childhood Classroomsmentioning
confidence: 99%
“…However, as Ladson-Billings (2014) asserts, educators often fail to carry out a critical and rigorous form of culturally relevant pedagogy (CRP) by neglecting the development of sociopolitical consciousness and attending solely to 'culture.' Especially in early childhood classrooms, teachers often find bringing in critical conversations around race and racism ('race talk') more difficult than 'culture talk' because they perceive that their students are too young to understand issues around racism and other forms of social injustice (Doucet & Adair, 2013;Husband, 2010;Kelly & Brooks, 2009;Nash & Miller, 2015;Ramsey, 2004). Ramsey (2004) further argued that early childhood education is not equipped with a clear vision and approach to teaching young children about racism.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown children recognize race and internalize racism at ages as young as 3 years old (Ausdale & Feagin, 2002). If elementary teachers do not engage children in critical examination of race and racism, the young learners may keep racially biased information they see and hear from the media, at home, or in school (Husband, 2010). They may believe that racism is not a significant concern in our society, thereby warranting no social action toward its rectification (Derman-Sparks & Ramsey, 2006).Although many elementary social studies topics, concepts, or issues can be taught and discussed through a critical racial lens (Garrett & Segall, 2015), in this article I focus on the topic of school segregation.…”
mentioning
confidence: 99%